Exploring how arithmetic operations in ancient Egypt through the history of Mathematics (Research, Society and Development, 2021)
With the encouragement of research, such as that of Costa & Lima (2016) and the National Common Curricular Base (BNCC), to incorporate history into the teaching of mathematics, one has the option of approaching Egyptian arithmetic as a way of (re) building some mathematical concepts in the classroom. The objective is to know the Egyptian arithmetic practice and to present proposals for activities on the multiplication and division operations in Egyptian mathematics. Thus, there is a qualitative methodology, of bibliographic and exploratory nature as to the objective. Thus, we contemplate a little of the context of ancient Egyptian civilization and its arithmetic processes used to solve various types of problems of the time. Therefore, it was found that this Egyptian arithmetic procedure can collaborate in the teaching of mathematics, so an activity session was elaborated on this subject to stimulate and propose an incorporation of the history of mathematics in teaching, as a resource provider, thus contributing to for student learning.